Major genera of plant parasitic nematodes associated with plantains and pineapple in the Huetar Norte and Huetar Atlántica regions of Costa Rica - Guzmán-Hernández, Tomás de Jesús (2014)
During this research, pineapple fields in the Región Huetar Atlántica (RHA) and the Región Huetar Norte (RHN) and plantain fields in the RHN were periodically sampled. The objective was to identify the major genera of plant parasitic nematodes that affect these crops, their frequency and population densities. At the same time, we explored the dynamics of the populations of major genera. Pratylenchus and Helicotylenchus had major frequency and the greatest densities of population in the pineapple fields, in both regions. The populations of both genera fluctuated in the RHN. In the RHA, populations of both genera increased and its increase could be explained with a polynomial function. In the plantain fields, the plant parasitic nematodes with major population densities and major incidence were Radopholus similis, Pratylenchus and Meloidogyne. The populations of these nematodes fluctuated in time as well.